2011
DOI: 10.1128/jvi.02316-10
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Evolution of HIV-1 in Breast Milk Determined by Single-Genome Amplification and Sequencing

Abstract: HIV transmission via breastfeeding accounts for a considerable proportion of infant HIV acquisition. However, the origin and evolution of the virus population in breast milk, the likely reservoir of transmitted virus variants, are not well characterized. In this study, HIV envelope (env) genes were sequenced from virus variants amplified by single-genome amplification from plasmas and milk of 12 chronically HIV-infected, lactating Malawian women. Maximum likelihood trees and statistical tests of compartmentali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
78
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 56 publications
10
78
0
Order By: Relevance
“…However, patient 3902 showed moderate to high neutralization potency at 9 months, with ID 50 s as high as 463. These results confirm that milk and plasma virus Envs have comparable neutralization sensitivities, as previously indicated by assessment of milk and plasma virus Env neutralization sensitivity using broadly neutralizing MAbs (55). The majority of the breast milk samples from uninfected lactating women displayed low levels of nonspecific HIV-neutralizing activity.…”
Section: Downloaded Fromsupporting
confidence: 87%
See 1 more Smart Citation
“…However, patient 3902 showed moderate to high neutralization potency at 9 months, with ID 50 s as high as 463. These results confirm that milk and plasma virus Envs have comparable neutralization sensitivities, as previously indicated by assessment of milk and plasma virus Env neutralization sensitivity using broadly neutralizing MAbs (55). The majority of the breast milk samples from uninfected lactating women displayed low levels of nonspecific HIV-neutralizing activity.…”
Section: Downloaded Fromsupporting
confidence: 87%
“…Thus, the role of neutralizing antibodies in vertical transmission of HIV is unclear. Viruses isolated from the breast milk and plasma of HIV-infected women have similar sensitivity to neutralization by broadly HIV-neutralizing monoclonal antibodies (MAbs) (55), but the ability of breast milk antibodies to neutralize autologous and heterologous HIVs has not been studied. Moreover, nonneutralizing antibodies, such as antibodies that mediate antibody-dependent cellular cytoxicity (ADCC) responses, may contribute to better clinical outcome and lower HIV/SIV load (2,17,41) and to the protection of vaccinated rhesus macaques against SHIV challenge (71).…”
mentioning
confidence: 99%
“…13,15 Others had similar findings for infants mostly infected intrapartum, though they only found differences in glycosylation sites and not variable loop lengths. 16 In this article, we present data on viral sequences from three mother-child pairs plus three additional infants where the infant became HIV DNA positive between 6 and 12 weeks postpartum through exposure to breast milk, with the goal of exploring whether known selective pressures influence this route of mother-to-child transmission.…”
mentioning
confidence: 72%
“…12,13 Data are very limited for breastfeeding pairs, but one study of three breast milk transmission events found a similar bottleneck for HIV-1 subtype A.…”
mentioning
confidence: 99%
“…All inferred genomes were intact and comprised of nine genes with open reading frames (LTR-gag-pol-vif-vpr-tat-rev-vpu-env-nef-LTR). Studies of these T/F virus sequences and progeny arising from them have given new fundamental insights into early virus evolution and the ontogeny of the antiviral immune response (1,26,31,34,46,56,66). We further hypothesized that the derivation with the Sequencher program (version 4.7; Gene Codes, Ann Arbor, MI) as previously described.…”
mentioning
confidence: 99%